Healthcare Professionals’ Knowledge, Attitude and Practice of Infection Prevention in Southwest Ethiopia - Tewodros Yosef (Environmental Health Insights, 2023)
Introduction: Infection prevention (IP) is a practical and scientifically supported technique to prevent avoidable infections. The effectiveness of IP techniques applied will depend on the knowledge, attitudes, and behaviors of healthcare professionals. Objective: This study aimed to assess the knowledge, attitude, and practice (KAP) of IP and its associated factors among healthcare professionals at Mizan-Tepi University Teaching Hospital (MTUTH) in southwest Ethiopia. Methods: A cross-sectional survey was conducted from September 1 and 15, 2021 among 196 healthcare professionals at MTUTH in south-west Ethiopia. The knowledge, attitude and practice outcome variables were measured using 13, 13, and 12 questions respectively. A logistic regression analysis was used. The level of significance was declared at a P  < .05. Results: The level of good knowledge, favorable attitude, and good practice of IP were 71.9%, 63.8%, and 53.6% respectively. Being a GP/specialist [adjusted odds ratio (aOR) = 10.6, 95% CI (2.13-52.9)] and the presence of an IP manual at work [aOR = 3.43, 95% CI (1.33-8.82)] were factors connected with good IP knowledge. The presence of sufficient PPE in the work area [aOR = 2.73, 95% CI (1.36-5.50)] and IP training [aOR = 3.05, 95% CI (1.28-7.29)] were factors associated with a favorable attitude toward IP. Good IP practice was linked to having enough personal protective equipment (PPE) in the workplace [aOR = 3.63, 95% CI (1.71-7.72)] and having good IP knowledge [aOR = 3.08, 95% CI (1.39-6.86)]. Conclusion: The level of KAP of IP among study participants was poor. The provision of adequate PPE, IP manuals and in-service training will help to improve the KAP of healthcare professionals toward IP. Therefore, the hospital management authority and other concerned stakeholders like local NGOs and regional health bureau should provide consistent support to the health professionals in terms of training, resources, and infrastructure to improve and integrate universal precaution in everyday services.